HRM devolution to middle managers: Dimension identification - Rosalía Cascón-Pereira; Mireia Valverde (BRQ Business Research Quarterly, 2014)
The phenomenon of devolution, or transfer of human resource management (HRM) responsibilities to middle managers (MM) has mainly been studied and measured as a homogeneous and unidimensional phenomenon. However, the variations found in the literature suggest that this key HR concept may be of a heterogeneous and multidimensional nature. This inductive study explores whether devolution may be broken down into different dimensions, beyond the simple addition of transferred areas (selection, training, etc.). To do so, case studies are carried out in the hospital sector. The results identify the existence of four dimensions of HRM devolution to MM: task execution, decision making power, financial power and knowledge transfer. A number of propositions around these dimensions are presented. The recognition of the multidimensional nature of the concept and the different degrees of transfer, around which a set of propositions is presented, is intended to act as the basis for subsequently carrying out explanatory, predictive studies."
Keywords: 650; Devolution; Middle managers; HRM function; Case study; Dimensions